Remdesivir Treatment for COVID 19 in Pregnant Patients with Moderate to Severe Symptoms: Serial Case Report - Yudianto Budi Saroyo; Amanda Rumondang; Irene Sinta Febriana; Achmad Kemal Harzif; Rima Irwinda (MDPI AG, 2021)
Introduction: Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2) infection that causes novel Coronavirus Disease 2019 (COVID-19) has become a major health problem worldwide and been declared a pandemic since March 2020 by WHO. One special population that poses a challenge is pregnant women with COVID-19. There have not been many studies related to COVID-19 in pregnancy. In this study, we present five serial cases of Remdesivir treatment for COVID-19 in pregnant women with moderate to severe symptoms. Case Illustration: We briefly describe five serial cases being treated with Remdesivir therapy during hospitalization. Four cases were delivered by cesarean section, and one was delivered vaginally in gestation week 37. All cases showed a shortened duration of hospitalization, rapid improvement in clinical symptoms, and no adverse events were observed in mothers, fetuses, and neonates. Discussion: Remdesivir, an inhibitor RNA Polymerase, has been used in COVID-19 treatment and is known to shorten recovery time in nonpregnant women. Some studies have shown no adverse effects on Remdesivir for pregnant women. Based on randomized control trial (RCT) during the Ebola epidemic, Remdesivir was safe to use for pregnant women. All cases showed reduced hospitalization time and better clinical outcomes without maternal, fetal, or neonatal adverse events. Conclusion: Remdesivir protocol for pregnant women with moderate to severe symptoms of COVID-19 has resulted in better clinical improvement with a shorter recovery period and no adverse effects during the hospitalization period. Further studies and RCT are warranted to evaluate the biosafety and effects of Remdesivir in pregnant women.